DETECTION OF ANCYLOSTOMA INFECTION IN APPARENTLY NORMAL POLICE DOGS - B.Dhivya; Bhaskaran Ravi Latha; P.Selvaraj; S. Abdul Basith (Indian Journal of Veterinary and Animal Sciences Research, 2025)
Coprological examination of the dogs of Chennai Police squad brought for routine health check up at the Madras Veterinary College Teaching Hospital, was done using flotation technique. Out of 59 samples screened for the presence of parasitic ova, 21 samples revealed the presence of Ancylostoma eggs. The positive samples were subjected to EPG studies using McMaster technique. High egg counts were evident in a few dogs while others showed medium level of infection. Eggs were subjected to morphometric studies. The hematological findings were correlated with EPG and the results were analyzed. The area where the dogs were housed was surveyed and the environmental factors which contributed to the recurrence of Ancylostoma infection in these dogs were assessed. A corrective measure to prevent further infection from the soil such as treatment of soil with sodium hypochlorite was advocated to the police. The response of the dogs after treatment was also evaluated.